2021
DOI: 10.3390/ma14174773
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Characterisation of Electrospun Polycaprolactone (PCL) and Poly(lactic-co-glycolic acid) (PLGA) Scaffolds for Vascular Tissue Engineering

Abstract: The current study aimed to evaluate the characteristics and the effects of degradation on the structural properties of poly(lactic-co-glycolic acid) (PLGA)-and polycaprolactone (PCL)-based nanofibrous scaffolds. Six scaffolds were prepared by electrospinning, three with PCL 15% (w/v) and three with PLGA 10% (w/v), with electrospinning processing times of 30, 60 and 90 min. Both types of scaffolds displayed more robust mechanical properties with increased spinning times. The tensile strength of both scaffolds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 86 publications
1
21
0
Order By: Relevance
“…In vitro results further confirmed that the M1 polarization of macrophages activated by the PCL framework was significantly weaker than that caused by the DBM framework. PCL is an FDA-approved polyester biomaterial ( Yadav et al, 2022 ) that has good biocompatibility and a relatively slow degradation rate with neutral and nontoxic degradation products ( Panigrahy and Rath, 2018 ; Backes et al, 2021 ; Bazgir et al, 2021 ), which may explain the low immunogenicity shown in this study. Although DBM is a natural biomaterial, during the production process, certain harmful bioactive components such as endotoxin and xenogenic protein are unavoidably retained to preserve the bioactivity of DBM ( Shi et al, 2018 ; Amirazad et al, 2022 ) ( Supplementary Figure S2 ), which might be why DBM triggered a more severe inflammatory response.…”
Section: Discussionmentioning
confidence: 86%
“…In vitro results further confirmed that the M1 polarization of macrophages activated by the PCL framework was significantly weaker than that caused by the DBM framework. PCL is an FDA-approved polyester biomaterial ( Yadav et al, 2022 ) that has good biocompatibility and a relatively slow degradation rate with neutral and nontoxic degradation products ( Panigrahy and Rath, 2018 ; Backes et al, 2021 ; Bazgir et al, 2021 ), which may explain the low immunogenicity shown in this study. Although DBM is a natural biomaterial, during the production process, certain harmful bioactive components such as endotoxin and xenogenic protein are unavoidably retained to preserve the bioactivity of DBM ( Shi et al, 2018 ; Amirazad et al, 2022 ) ( Supplementary Figure S2 ), which might be why DBM triggered a more severe inflammatory response.…”
Section: Discussionmentioning
confidence: 86%
“…However, the rate of scaffold degradation depends on the components and their proportion in the scaffold. According to Bazgir et al [ 52 ], PCL nonwoven electrospun membrane of thickness 0.11 mm lost about 20% of its weight for 12 weeks degradation in PBS in a room temperature. Pogorielov et al [ 53 ] found that PCL nanofibrous matrices lost 38 ± 5% of their mass during degradation in simulated body fluid for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that some PEG residues were still present and cross-linked within the electrospun mat when exposed to surrounding UV light, thus trapping the fibers deep inside and modifying the properties of the material. PCL biodegradability could ultimately contribute to decreasing the mechanical properties of the scaffold to a physiological range and promote neotissue formation [ 40 , 41 ]. However, this raises the question of the different rate of biodegradability of the PCL and PEG [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%